The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1038/s41598-017-18101-7
|View full text |Cite|
|
Sign up to set email alerts
|

Snail collaborates with EGR-1 and SP-1 to directly activate transcription of MMP 9 and ZEB1

Abstract: The Snail transcription factor plays as a master regulator of epithelial mesenchymal transition (EMT), one of the steps of tumor metastasis. Snail enhances expressions of a lot of mesenchymal genes including the matrix degradation enzyme matrix metalloproteinases 9 (MMP9) and the EMT transcription factor zinc finger E-box binding homeobox 1 (ZEB1), however, the underlying mechanisms are not clarified. Herein, we investigated how Snail upregulated transcription of ZEB1 and MMP9 induced by the tumor promoter 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 40 publications
(53 reference statements)
2
66
0
Order By: Relevance
“…ZEB1 induces the promotion of EMT and in combination with other factors triggers metastasis [ 25 ] and is highly expressed in aggressive cancer cell lines [ 1 ] and the overexpression of the protein may be an indicator of poor prognosis in breast, pancreatic, and lung cancer [ 21 ]. What is more, a mutual regulation between SNAI1 and ZEB1 has been recently identified [ 25 ]; SNAI1, acting as a primary EMT regulator, may enhance expression of other transcription factors, including ZEB1 and TWIST [ 27 ]. In metastatic cell nucleus, ZEB1 and TWIST1 proteins prevent E-cadherin gene transcription [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZEB1 induces the promotion of EMT and in combination with other factors triggers metastasis [ 25 ] and is highly expressed in aggressive cancer cell lines [ 1 ] and the overexpression of the protein may be an indicator of poor prognosis in breast, pancreatic, and lung cancer [ 21 ]. What is more, a mutual regulation between SNAI1 and ZEB1 has been recently identified [ 25 ]; SNAI1, acting as a primary EMT regulator, may enhance expression of other transcription factors, including ZEB1 and TWIST [ 27 ]. In metastatic cell nucleus, ZEB1 and TWIST1 proteins prevent E-cadherin gene transcription [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kukoamine A significantly reduced the expression of mesenchymal markers such as snail, vimentin, and N‐cadherin and increased the expression of epithelial markers such as E‐cadherin and subsequently inhibited the migration of human GBM U251 and WJ1 cells . Jorda et al indicated that snail bound to the promoter region and enhanced the expression of MMP‐9 in Madin Darby canine kidney epithelial cells and Hep G2 cells. Snail also upregulated the expression of MMP‐2 in hepatocellular carcinoma cells .…”
Section: Discussionmentioning
confidence: 99%
“…Next, we deciphered the generic emergent properties of an extended gene regulatory network involving SNAIL, SLUG, ZEB1, miR-200 and E-cadherin (CDH1) (Fig 4A). At a transcriptional level, ZEB1, SNAIL and SLUG can all repress E-cadherin [Batlle et al, 2000;Sterneck et al, 2020;Mooney et al, 2016], and SNAIL and SLUG can activate ZEB1 [Wels et al, 2011;Wu et al, 2017]. Further, SLUG is known to self-activate [Kumar et al, 2015], but SNAIL selfinhibits [Peiró et al, 2006].…”
Section: The Role Of Slug In Stabilizing Hybrid E/m State Is a Functimentioning
confidence: 99%